A new Throne-Amulet from Hedeby: First Indication for Viking-age Barrel-chairs - Kalmring, Sven (Danish Journal of Archaeology, 2019)
In 2017 a throne-amulet made from bone, once retrieved from the diggings of harbour excavation 1979/80 in Hedeby, was committed to the Wikinger Museum Haithabu. It constitutes the second specimen known from the site and fits well into the larger group of throne-amulets known from south-eastern Scandinavia. The academic discussion of these amulets as devotional pagan objects either in connection with the worship of Óðinn or else as thrones of vǫlur is controversial. The piece from Hedeby harbour does not seem to depict the typical block-chair, though, but is about the first indication for the existence of Viking-age barrel-chairs used continuously until Early modernity.